A review of research and development on titanium microalloyed high strength steels. (22nd June 2018) - Huo, Xiangdong; Xia, Jinian; Li, Liejun; Peng, Zhengwu; Chen, Songjun; Peng, Ching-Tun
Abstract: In this paper, the development status of titanium microalloyed high strength steels is comprehensively introduced, and the precipitation behaviors of titanium, including the strain-induced precipitation and interphase precipitation of nano-sized carbides, are illustrated in detail. Moreover, the future trend of titanium microalloying technology is also discussed, which provides insightful suggestions for not only the prospective developments but also the potential industrial applications of these titanium microalloyed steels.